2020
DOI: 10.3390/ijerph17176098
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Relationships between Problematic Alcohol Use and a Problematic Use of Video Games, Social Media and the Internet and Their Associations to Mental Health in Adolescence

Abstract: Adolescents frequently show risky behavior, and these problematic behavior patterns often do not occur in isolation, but together. Problematic alcohol use is widespread among youth, as is problematic use of the Internet and of specific online applications (video games or social media). However, there is still a lack of findings for minors regarding the relations between these behavioral patterns (particularly between problematic alcohol use and problematic gaming or problematic social media use). Standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…Albeit a small association, this correlation indicates that students who do not feel of importance to others may use social media compulsively, perhaps as a way to feel significant via an online presence. This notion corresponds to previous findings indicating that social media addiction is linked to lower levels of self-esteem (Banyai et al, 2017;Wartberg & Kammerl, 2020). In addition, researchers have found a positive correlation between social media addiction and difficulties in emotion regulation among adolescents (Wartberg et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Albeit a small association, this correlation indicates that students who do not feel of importance to others may use social media compulsively, perhaps as a way to feel significant via an online presence. This notion corresponds to previous findings indicating that social media addiction is linked to lower levels of self-esteem (Banyai et al, 2017;Wartberg & Kammerl, 2020). In addition, researchers have found a positive correlation between social media addiction and difficulties in emotion regulation among adolescents (Wartberg et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Social media addiction has been associated with a variety of detrimental outcomes, including low self-esteem and depressive symptoms (Banyai et al, 2017), fear of missing out and emotion regulation difficulties (Pontes et al, 2018), and delay discounting (i.e., the preference for smaller immediate rewards over larger but delayed rewards; Turel et al, 2018). Among adolescents, Wartberg and Kammerl (2020) found significant associations between problematic social media use and a variety of variables, including antisocial behavior, emotional distress, self-esteem issues, and problematic internet gaming. Additionally, among a sample of Turkish adolescents, researchers found that social media addiction significantly correlated with more depression and less self-esteem (Kircaburun, 2016).…”
Section: Social Media Addiction and Mental Healthmentioning
confidence: 99%
“…In addition to practical problem-solving strategies, dysfunctional stress management strategies are often used to address these developmental tasks while also dealing with the struggle for freedom (from parental restraints, for example) or self-discovery. Given the pervasive pattern of problematic behaviors associated with adolescent digital media use, it seems quite appropriate to test whether there is an empirical relationship [10]. Addressing the issue of online gaming and the issue of mental health consequences children and adolescents playing online games is important given the usual trajectory of neurodevelopment; adolescence is characterized by increased maturation of the limbic system, which makes adolescents more likely to engage in addictive behavior than adults [11].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies indicate a strong association between Internet use disorders and both internalizing and externalizing disorders (e.g., Carli et al, 2013 ; Masi et al, 2020 ; Paschke et al, 2020 ). The most frequently mentioned mental illnesses associated with Internet use disorders are ADHD, depression, and anxiety disorders with social anxiety in particular ( Taranto et al, 2015 ; Lindenberg et al, 2017b ; So et al, 2017 ; Franke et al, 2018 ; Masi et al, 2020 ; Wartberg and Kammerl, 2020 ). The associations between Internet use disorders and internalizing disorders is subject matter in the present study, as (social) anxiety as well as depression rank among the most common mental disorders in German children and adolescents ( Beesdo et al, 2007 ; Klasen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%